Model pemantauan serahan berasaskan wajaran bagi proses pembangunan perisian - Megat Azrin Ahmad (Tanjong Malim, 2019)
Model pemantauan serahan berasaskan wajaran bagi proses pembangunan perisian by Megat Azrin Ahmad